Amyloid nomenclature 2018: recommendations by the International Society of Amyloidosis (ISA) nomenclature committee. (2nd October 2018) - Benson, Merrill D.; Buxbaum, Joel N.; Eisenberg, David S.; Merlini, Giampaolo; Saraiva, Maria J. M.; Sekijima, Yoshiki; Sipe, Jean D.; Westermark, Per
Abstract: The nomenclature committee of the International Society of Amyloidosis (ISA) meets every second year to discuss and formulate recommendations. The conclusions from the discussion at the XVI International Symposium on Amyloidosis in Kumamoto, Japan, 25–29 March 2018 and afterwards are summarized in this Nomenclature Article. From having recommended the use of the designation "amyloid fibril" for in vivo material only, ISA's nomenclature committee now accepts its use more broadly following the international scientific literature. However, it is important always to stress the origin of the β-fibrils in order to avoid misunderstanding. Given the more broad use of the word "amyloid" several classes of amyloid fibrils may be distinguished. For the medical in vivo situation, and to be included in the amyloid nomenclature list, "amyloid" still means mainly extracellular tissue deposits of protein fibrils, recognized by specific properties, such as green-yellow birefringence after staining with Congo red. It should also be underlined that in vivo amyloid fibrils, in addition to the main protein contain associated compounds, particularly serum amyloid P-component (SAP) and proteoglycans, mainly heparan sulfate proteoglycan. With this definition there are presently 36 human amyloid proteins of which 14 appear only associated with systemic amyloidosis and 19 as localized forms. Three proteins can occur both as localized and systemic amyloidosis. Strictly intracellular aggregates are not included in this list.